Relationship of aggregated intramembranous particles to water permeability in vasopressin-treated toad urinary bladder. - Kachadorian, W A (1977)
It has been previously demonstrated with freeze-fracture electron microscopy that vasopressin induces specific structural alterations of the luminal membrane of granular cells from toad urinary bladder in a dose-dependent fashion. These alterations consist of aggregated intramembranous particles and are observed both in the presence and absence of an osmotic gradient. We examined the effect of methohexital, a selective inhibitor of vasopressin-stimulated water flow, and the effect of phloretin, a selective inhibitor of urea permeability, on the structure of the granular cell luminal membrane. Methohexital treatment of the vasopressin-stimulated toad bladder reduced both the osmotic water flow and vasopressin-induced alterations of membrane structure to the same extent. Phloretin reduced urea permeability but not water flow or particle aggregation. Since neither agent affects vasopressin-stimulated sodium movement, these findings indicate that the phenomenon of particle aggregation is specifically related to vasopressin-induced water permeability and not to changes in urea or sodium permeability.